L1 adaptive control design of a helicopter in vertical flight. (November 2020) - Tian, Song; Wang, Jiang; Lin, Defu; Pei, Pei
This article presents L 1 adaptive control scheme for vertical flight control of helicopter. Linear controller is designed as baseline controller to provide preliminary improvement in performance and robustness. Considering the existence of uncertainties and disturbances, we propose L 1 adaptive controller with modified piecewise constant adaptation law to augment the baseline controllers. Further, the proposed L 1 adaptive controller can be implemented without any modification of the baseline controller. Benefit from this, the design of the entire control system is significantly simplified, and the designed controller is easy to apply to practical engineering. The simulation results indicate that the proposed controllers have good performance for helicopter vertical flight in the presence of uncertainties and disturbances.